Magnetic Solid-Phase Extraction Based on β-Cyclodextrins/Acrylic Acid Modified Magnetic Gelatin for Determination of Moxidectin in Milk Samples - Yinzhu Shang; Jing Luo; Peng Wang; Xiaoya Zhao; Cheng Ye; Shaofei Guo (Journal of Analytical Methods in Chemistry)
β-Cyclodextrins/acrylic acid modified magnetic gelatin was prepared and then employed as the magnetic solid-phase extraction (MSPE) sorbent for extraction of moxidectin in milk samples. Due to the rigidity of hydrophobic cavity of β-cyclodextrins and carboxyl groups of acrylic acid, magnetic composites are prepared to form a complex with target molecules through various kinds of chemical reactions and then showed excellent extraction performance. This method exhibits the advantages of simplicity of implementation, short extraction time (5 min), low solvent consumption, and high extraction efficiency. A rapid, simple, and effective method for the analysis of moxidectin in milk samples was established by MSPE coupled with liquid chromatography-fluorescence detection. The limit of detection was 0.1 ng·mL−1 and the recoveries from milk samples were in the range of 93.8%–112.5%. The relative standard deviation was not higher than 6.4%. In conclusion, magnetic solid-phase extraction is a simple and robust preconcentration technique that can be coupled to other analytical methods for the quantitative determination of target molecules in complex samples.